Socio-environmental program and the principles of relationship with stakeholders - Bogo, Adelaide (2017)
It is common nowadays for organizations to demonstrate socially responsible behavior based on relationships with stakeholders. These relationships, in turn, are based on two relationship principles, Corporate Legitimacy and Fiduciary Stakeholder. At their core, these two principles lead to the duty of managers to manage the company in order to serve the stakeholders. Based on this view, Termotécnica, a company that uses expanded polystyrene (EPS) in its production process, has developed the Recycle EPS program. Based on this information, this study will demonstrate how a socio-environmental recycling program contributes to these two principles. This is a unique case study, supported by the theoretical proposition that socio-environmental programs meet the stakeholder relationship principles. It adopts the content analysis technique and the Nvivo system to assist in the organization and analysis of data. The results indicate that the Recycle EPS program provides managers with corporate legitimacy and ensures trust in fiduciary relationships, and therefore the social license to operate.